Kajian Etnomusikologi Alat Musik Canang Ceureukeh sebagai Warisan Musik Tradisional Kota Lhokseumawe, Aceh - Naura Atkiya; Mifta Maisuri; Koyimatul Khasanah; Hafiz Alista; Rahmiyatun Nisa; Miftahul Khairani Irsa; Yuli Astuti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study discusses Canang Ceureukeh , a traditional music form originating from Lhokseumawe City, Aceh. The research aims to explore the musical structure of Canang Ceureukeh , its social functions and cultural values, public perception in the modern era, and the challenges and efforts related to its preservation. A descriptive qualitative approach was used, with ethnographic methods involving observation, interviews, and documentation in two main locations: Gampong Hagu Teungoh and Gampong Ulee Jalan. The results show that Canang Ceureukeh is performed in groups using canang (small gongs), drums, and serunee (Acehnese wind instruments), characterized by fast rhythms and vocal improvisation. It serves as entertainment, a vehicle for moral messages, and a cultural identity marker. While the older generation still values this music tradition, interest among younger people is declining due to modern musical influences. Preservation efforts are ongoing through village art centers, but they face obstacles such as lack of regeneration and limited institutional support. The study concludes that Canang Ceureukeh is a valuable cultural heritage that requires serious attention for its preservation.